Impact of low serum calcium at hospital admission on SARS-CoV-2 infection outcome. (March 2021) - Torres, Berta; Alcubilla, Pau; González-Cordón, Ana; Inciarte, Alexy; Chumbita, Mariana; Cardozo, Celia; Meira, Fernanda; Giménez, Marga; de Hollanda, Ana; Soriano, Alex; ,; Albiach, Laia; et al.
Highlights: Almost two thirds of patients with SARS-CoV-2 infection present with hypocalcemia at hospital admission. Hypocalcemia at admission is related to high oxygen support requirement at any time point during hospitalization. Patients with hypocalcemia had two times more probability to be admitted to the Intensive Care Unit during hospitalization. Abstract: Background: Calcium is an essential ion for pathogen survival and virulence and is involved in the regulation of the inflammatory response. Hypocalcemia is a common laboratory finding in critically ill patients. Data regarding levels of calcium in SARS-CoV-2 infection is scarce. Patients with SARS-CoV-2 infection who present with hypocalcemia could have a worse outcome. Methods: We performed a retrospective analysis of hospitalized patients with SARS-CoV-2 infection and included all patients who had any serum calcium measurement in the first 72 h since hospital admission. The main objective was to investigate the relation of low serum calcium with adverse outcome, measured by the requirement of high oxygen support – defined as high flow nasal cannula oxygen, non-invasive mechanical ventilation and/or invasive ventilation – intensive care unit admission or death. Results: A total of 316 patients were included in the study. Median age was 65 years (IQR 55–74); 65% were men. Hypocalcemia within 72 h since hospital admission was present in 63% of patients. A higher number of patients in the hypocalcemia group required high oxygen support during hospitalization (49% vs 32%; p = 0, 01) and were admitted to the ICU (42% vs 26%; p = 0, 005). No differences in mortality were observed between groups. Conclusions: Hypocalcemia is frequent in hospitalized patients with SARS-CoV-2 infection and can identify patients who will have a worse outcome. More studies are needed to understand the role of calcium metabolism in SARS-CoV-2 infection and to address the clinical implications and therapeutic interventions it might have.